Disparities in utilization of sexual and reproductive health services among high school adolescents from youth friendly service implemented and non-implemented areas of Southern Ethiopia - Bayu Haile; Mulugeta Shegaze; Tesfaye Feleke; Mustefa Glagn; Eshetu Andarge (BMC, 2020)
Abstract Background In recent years, much effort was made to improve access to sexual and reproductive health services (SRH) to adolescents and youths in Ethiopia particularly through establishment of youth friendly service (YFS) corners as part of the existing health care facilities. The existing evidences focused on investigating the utilization of SRH services at YFS established areas alone. There is a dearth of evidence which compares the SRH service use between the YFS implemented and non-implemented areas so that evidences can be drawn to suggest on the successes of the expansion of youth friendly corners. Methods A school-based comparative cross-sectional study was conducted by employing a multistage cluster sampling method. A pre-tested self-administered questionnaire was used to collect data and the collected data were entered in to Epidata version 4.4.1 software and then exported to SPSS version 20 for analysis. χ2 test was used to see a significant difference in SRH service utilization among adolescents from YFS implemented and non-implanted areas. The association between the SRH services utilization and the independent variables were examined using binary logistic regression. Finally, variables having p-value less than or equal to 0.05 in the multivariable logistic regression model were considered as statistically significant. Results There were a significant difference in the rate of SRH service utilization between YFS implemented (33.8%) and YFS non- implemented (9.9%) areas (χ2 = 37.49, p < 0.001). Higher educational status of mothers (AOR = 2.588, 95% CI: 1.220, 5.491), having open discussion with family (AOR = 3.175, 95%CI: 1.624, 6.206), having good knowledge (AOR = 4.511, 95% CI: 2.458, 8.278) and having positive attitude (AOR = 5.084, 95% CI: 2.764, 9.352) were factors positively associated with SRH services utilization. Conclusion Compared with high schools from YFS implemented areas, the SRH service utilization was significantly lower among students from high schools where health facilities did not implement YFS. There is a need for enhancing efforts to establish YFS corners by the stakeholders at different hierarchies at places where the centers were not established so that SRH service uptake would be improved. In addition, it is better to promote open discussion with adolescents at the family level, and emphasis should be given for women education in the broad sense. Furthermore, wide-range awareness creation strategies should be used to address poor knowledge and negative attitude.